Treatment of Edema Formation in Oncology - Schnell, Oliver; Tonn, Jörg Christian (Elsevier, 2017)
Brain edema formation is a pivotal characteristic which accompanies brain tumors of different etiologies. Primary brain tumors or brain metastases are fastly growing malignancies that may lead to extensive vasogenic brain edemas resulting in mass effects with midline-shift and life-threatening brain herniation within a short time period. However, even benign tumors like meningiomas often cause severe brain edema comprising the functional integrity of the brain and leading to significant clinical deterioration. Therefore, one of the major goals for clinicians considering brain edema therapy is to decrease edema formation and increase edema resolution in order to avoid further aggravation of clinical and functional impairment caused by the edema and its aftermath. Yet, due to anatomo-functional aspects of the brain and its bony encasement in the skull treatment of brain edema is essential but at the same time limited in several ways, as will be discussed in this chapter.
CRIS-Team Scopus Importer:2023-09-13
Keywords: brain herniation; brain metastasis; Brain tumors; dexamethasone; functional integrity; gliomas; hydrocephalus; symptomatic therapy